Social Welfare Administration in India - Sachdeva, D.R (New Delhi, 1992)
This book is about social welfare embedded in charty, philanthropy, religion and cuture of our people since time immemorial and the patronage that enjoyed of some welfare oriented rulers of ancient and medieval eras.
Keywords: Welfare administration